Effect of anesthetics on postoperative nausea and vomiting after peripheral vascular surgery in end-stage renal disease patients: A retrospective observational study - Cho, Ho Bum; Park, Sun Young; Kim, Nayoung; Choi, Sang Jin; Song, Sanghoon; Yoo, Jae Hwa; Kim, Mun Gyu; Chung, Ji Won (Frontiers in Surgery, 2022)
Background: Propofol-based total intravenous anesthesia (TIVA) is considered a prophylactic approach to decrease postoperative nausea and vomiting (PONV). Despite general anesthesia commonly being performed in end-stage renal disease (ESRD) patients, PONV in ESRD patients has not been well-described. We investigated PONV in peripheral vascular surgery under general anesthesia in ESRD patients. Methods: To compare PONV between propofol-based TIVA and anesthesia with volatile anesthetics, we collected retrospective data from patients who underwent peripheral vascular surgery under general anesthesia from July 2018 to April 2020. We performed univariable and multivariable analyses, including factors that could be associated with PONV and those previously shown to affect PONV. Result: A total of 1,699 peripheral vascular surgeries under general anesthesia in ESRD patients were eligible for analysis. Based on the multivariable analysis, TIVA (odds ratio [OR], 0.45; 95% confidence interval [CI], 0.35–0.60; P<0.001) significantly decreased PONV. Female sex (OR, 1.85; 95% CI, 1.44–2.38; P<0.001) and anesthetic duration (OR, 1.01; 95% CI, 1.00–1.01; P<0.001) were associated with increased PONV. Conclusion: Propofol-based TIVA is the most influential factor decreasing PONV after peripheral vascular surgery in ESRD patients. Anesthesiologists can apply propofol-based TIVA as an alternative to anesthesia with volatile anesthetics.